2015
DOI: 10.1002/jor.23099
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage repair with recombinant human type II collagen/polylactide scaffold in a preliminary porcine study

Abstract: The purpose of this study was to investigate the potential of a novel recombinant human type II collagen/polylactide scaffold (rhCo-PLA) in the repair of full-thickness cartilage lesions with autologous chondrocyte implantation technique (ACI). The forming repair tissue was compared to spontaneous healing (spontaneous) and repair with a commercial porcine type I/III collagen membrane (pCo). Domestic pigs (4-month-old, n ¼ 20) were randomized into three study groups and a circular full-thickness chondral lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Therefore, a combined material may solve this problem. Moreover, concerns about cell division, proliferation, and migration, as well as biodegradability continue to remain unsolved [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a combined material may solve this problem. Moreover, concerns about cell division, proliferation, and migration, as well as biodegradability continue to remain unsolved [1012].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the yarn-collagen/HA scaffolds could enhance cartilage differentiation of MSCs. Muhonen et al [109] prepared the collagen-PLA scaffold with recombinant human type II collagen. Then, they explored the potential of the scaffold in the repair of full-thickness cartilage lesions without additional cells compared to spontaneous healing and repair with a commercial porcine type I/III collagen membrane.…”
Section: Typical Applications Of Collagen-based Scaffold In Tissuementioning
confidence: 99%
“…Collagen is the main protein of most tissues and contributes to the physical support of tissues [ 142 ]. Therefore, collagen is widely used as a material for nerve [ 143 , 144 , 145 ], bone [ 146 , 147 , 148 ], cartilage [ 149 , 150 , 151 , 152 ], tendon [ 153 ], ligament [ 154 , 155 ], or skin [ 156 , 157 ] tissue engineering. Chen et al report that the expression of proangiogenic growth factors and the transcript of MMP of human breast MCF-7 cancer cells cultured on collagen sponges increased [ 158 ].…”
Section: 3d Culture System Of Cancer Cells With Biomaterialsmentioning
confidence: 99%